(untitled) (East West Medical College Journal, 2026)
Hypothyroidism is common during pregnancy. Maternal and fetal complications are higher in women with hypothyroidism compared to euthyroid women. So optimal maternal thyroid function during pregnancy is important for both the mother and the fetus. This observational study aimed to study the foetomaternal outcome among pregnant hypothyroid women. It was carried out in the department of Obstetrics and Gynaecology in Ad-din Women’s Medical College Hospital, Maghbazar, Dhaka from Ist July 2024 to 30 th June 2025. The study included 108 hypothyroid pregnant women to observe fetal and maternal effects of hypothyroidism. Patients were collected as per inclusion and exclusion criteria after informed written consent. Maternal complications like preeclampsia, postpartum haemorrhage, gestational hypertension, anaemia and postpartum depression were common in hypothyroid pregnant women .on the other hand, adverse fetal outcome, such as preterm birth, abortion, IUGR, respiratory distress and still birth were common in hypothyroid cases. To prevent these adverse fetomaternal outcome routine maternal thyroid function testing should be done as early as possible. EWMCJ Vol. 14, No. 2, July 2026: 183-186